Perlindungan Protein Menggunakan Tanin dan Saponin Terhadap Daya Fermentasi Rumen dan Sintesis Protein Mikrob (PROTECTION OFPROTEINUSINGTANNINS AND SAPONINS OF RUMEN DIGESTIBILITYAND MICROBESSYNTHESISPROTEIN) - Ani, Ana Shofi; Pujaningsih, Retno Iswarin; ., Widiyanto (Jurnal Veteriner; Vol 16 No 3 (2015), 2015)
The objective of this experiment was to examine protection of protein using tannins and saponins toimprove rumen digestibility and microb-mediated protein synthesis in vitro. Rumen fluids used as inoculumwas collected from a composite of two female adult fistulatedongole cattle weighed of ±300 kg with theage of five years old. The experimental design used in this study was a completely randomized design withsix treatments and three replication of each treatment. The six treatments consisted of T0: Proteinconcentrates without protection, T1: protein concentrates protected with 1.2% saponin, T2: proteinconcentrates protected with 0.5% tannin and 0.9% saponin , T3: protein concentrates protected with 1.0%tannin and 0.6% saponin, T4: protein concentrates protected with 1.5 % tannin and 0.3% saponin and T5:protein concentrates protected with 2.0% tannins. The result showed that treatment with tannin, saponinand their combination had a significantly affect (P<0,05) on the level of ammonia (NH3), the total volatilefatty acids (VFA), and total protein. Protection of proteins with combination of 1,0% tannin and 0.6%saponin resulted in best effect on feed protein as shown by its NH3 concentration, total VFA and totalprotein. This indicates the level of protection of feed protein can improve rumen digestibility and microbesmediatedprotein synthesis, as showed in the concentration of N-NH3, total VFA and total protein.
Keywords: protection, tannins, saponins, rumen digestibility, microbes protein synthesis